Educational assesment in training of competent doctors in ukraine: problems and their decision - Kulbashna Yaroslava; Astapenko Olena (Borys Grinchenko Kyiv Metropolitan University, 2016)
In article deals with the problem of the use of educational assessment in the training of future doctors in Ukraine. The key role of educational assessment in the improvement of the quality of higher medical education was defined. The basic stages of educational assessment methods in historical perspective are presented. Specifies, that educational assessment is one of the components of educationalexpertise. Analysis the use of the most common method of educational assessment - testing was found, that it plays an important but only supporting role in determining the level of formation of professional competence of future doctor. The successful experience of foreign countries indicates that for the increasing of objectiveness of the educational outcomes estimation need to get information from multiple information sources. Above all, to confirm the academic achievements of future doctors is necessary at first to base on their self- assessment. These data are supplemented with the preliminary assessment of teachers, the results of the test control and eventually should be interpreted and compared with current estimates in discipline. Such integrated approach helps identify problematic aspects of the future doctors training, find decisions to remove them and draft the perspectives of future learning outcomes. Besides, the development of tests should be based on the principles of competence approach, focusing on the mechanisms of multiple knowledge integration and practical orientation of them. The analysis of scientific sources and own teaching experience shows that the effectiveness of solving problems in educational assessment in high medical school, including dental education, largely depends on the creation of a comprehensive system of quality assessment of higher medical education at the national level, expert teams in each higher medical schools; implementation of integrated and differentiated approach into the process of educational assessment; training of experts in field of educational assessment. Decreasing of efficiency test method is seen in insufficient theoretical and methodological support of educational assessment process in general and testing process in particular.